Comparison of the Urodynamic Patterns of the Disorders Frequently Encountered in the Field of Pediatric Urology - Hasan Demirkan; Mehmet Ozgur Kuzdan (Haseki Tıp Bülteni)

(untitled)
Aim:There is still a lack of sufficient evidence-based data on the standardized urodynamic patterns of urological disorders worldwide, particularly in the childhood age group. With this study, we sought to investigate the outcomes of urodynamic studies of common disorders frequently encountered in pediatric urology practice.Methods:Children who underwent urodynamic studies in a pediatric urology unit between March 2019 and September 2020 were included in the study. A retrospective review of data on demographic characteristics and cystometrogram findings of 266 children from the urodynamic laboratory database was performed.Results:The diagnoses of the patients were vesicoureteral reflux (VUR) (n=120), spinal dysraphism (SD) (n=94) and day-time incontinence (DI) (n=28). Twenty-four patients who had other than these diagnoses were excluded. While there was no statistically significant difference between VUR-DI cases (p=0.31) and DI-SD cases (p=0.1) regarding bladder compliance, it was noteworthy that bladder compliance was diminished in the SD group when compared to the VUR group (p<0.001). The presence of idiopathic detrusor contraction (IDC) suggesting overactive bladder was also compared and no significant difference was found between the groups (p=0.084).Conclusion:The results of our study contribute the literature for urodynamic manifestations that are still challenging to standardize in children with urologic disorders because of the variety of outcome measures and multitude of urodynamic parameters used. We also announce that the IDC is a noteworthy pattern of neurogenic as well as non-neurogenic urological disorders.